1979
DOI: 10.1111/j.1699-0463.1979.tb02404.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Acute Salpingitis in Grivet Monkeys Provoked by Chlamydia Trachomatis

Abstract: Chlamydia trachomalis is a common cause of sexually transmitted diseases. Recently it has been shown that chlamydiae are also responsible for complications to such lower genital tract infections. In this study, isolates of C. trachomatis from the fallopian tubes of patients with acute salpingitis were inoculated direct into the fallopian tubes of two, and through the cervical canal into the uterine cavity of one grivet monkey. The experimental infections resulted in a self‐limited acute salpingitis in the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…By directly inoculating the fallopian tubes and the endometrial cavity, grivet monkeys developed acute self-limited salpingitis. The histological findings in the tubal tissues post-inoculation (infiltration of the subepithelial and mucosal epithelium, abundant lymphocytes, and polymorphonuclear (PMN) leukocytes, and exudate in the tubal lumen with small clusters of desquamated epithelium) mirrored what is considered to be the hallmark signs of acute salpingitis in women [ 32 ]. Moller also showed that there was an activated immune response associated with inoculation with C. trachomatis .…”
Section: Development Of Pid In Nhpsmentioning
confidence: 99%
See 1 more Smart Citation
“…By directly inoculating the fallopian tubes and the endometrial cavity, grivet monkeys developed acute self-limited salpingitis. The histological findings in the tubal tissues post-inoculation (infiltration of the subepithelial and mucosal epithelium, abundant lymphocytes, and polymorphonuclear (PMN) leukocytes, and exudate in the tubal lumen with small clusters of desquamated epithelium) mirrored what is considered to be the hallmark signs of acute salpingitis in women [ 32 ]. Moller also showed that there was an activated immune response associated with inoculation with C. trachomatis .…”
Section: Development Of Pid In Nhpsmentioning
confidence: 99%
“…Moller also showed that there was an activated immune response associated with inoculation with C. trachomatis . The antibody response was that of a primary infection with an IgM to IgG antibody seroconversion [ 32 ]. Additionally, in the animal that was infected in the endometrial cavity they documented ascent of the C. trachomatis to the fallopian tubes.…”
Section: Development Of Pid In Nhpsmentioning
confidence: 99%
“…Nonhuman primates, including the marmoset, grivet, and pigtailed macaque, have been used as models for C. trachomatis genital tract infection for decades and would intuitively be the closest surrogate models for humans. Infection in grivet monkeys elicited acute salpingitis after inoculation into either the fallopian tube directly or the uterine cavity [67]. Studies on the mode of spread of chlamydial infection continued in the grivet model [68].…”
Section: Animal Models Of Chlamydial Infectionmentioning
confidence: 98%
“…trachomatis infections, including the marmoset, grivet and baboon, and pigtailed macaque. The pigtailed macaque model was initially developed by Patton and colleagues; it has been the most frequently used primate model for genital Chlamydia research (Ripa et al 1979; Bell et al 2011; De et al 2013). C. trachomatis can naturally infect this macaque species without hormonal pretreatment, and the infected macaques develop cervicitis and salpingitis, which are highly similar to genital tract inflammation in humans.…”
Section: Animal Models Of Chlamydial Pathogenesismentioning
confidence: 99%